Sonhos do Idealismo Alemão explicados pela "terra dos sonhos" (Revista Eletrônica Estudos Hegelianos, 2023)
Considering the influence of Eastern thought on modernity, mainly Chinese philosophies in 18th century France and Indian philosophy in 19th century Germany, we will be able to trace the origin of German interest in India, while such fascination arises from colonial fantasies, based above all on an idealistic approach and imagination about the other, This philosophy project can find in Hindu and Vedic speculations a form of contrast and recognition of itself. In this brief article, we intend to understand to what extent the definition given to India by Hegel with the concept of “idealism of the imagination” and “land of dreams”, actually reflects the self-understanding of German Idealism philosophy. German Idealism thus hides, in its own constitution and formulation, a fascination and projection of what was understood as Hindu thought. Keywords: Philosophy - German Idealism – India